2021
DOI: 10.1097/phm.0000000000001743
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Bracing for Chronic Low Back Pain

Abstract: Purpose We performed this study to evaluate the effect of back bracing to treat patients with chronic low back pain. Methods This was a prospective, unblinded, randomized controlled trial of 61 adults with uncomplicated chronic low back pain (>12 wks) and imaging findings of degenerative spondylosis, to assess the effectiveness of a semirigid back brace. All study participants received back school instruction. The treatment group also received a lumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Regarding low back pain, different study protocols reported a positive effect of lumbar orthosis in 115 patients [2,6,18,21]. In contrast, four different randomized studies did not provide any pain relief after six months observation of 266 patients [8,14,17,30]. No positive effect of wearing a lumbar orthosis on muscle thickness measured by ultrasound was reported in 44 patients [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding low back pain, different study protocols reported a positive effect of lumbar orthosis in 115 patients [2,6,18,21]. In contrast, four different randomized studies did not provide any pain relief after six months observation of 266 patients [8,14,17,30]. No positive effect of wearing a lumbar orthosis on muscle thickness measured by ultrasound was reported in 44 patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…All meta-analyses and literature research reviewed did not provide medical or technical differentiation [1,6,8,[11][12][13][14][15][16][17][18][19]24,26,27]. Thus, general orthotic designations such as "lumbar support" are used in the following.…”
Section: Overview Of the Current Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The authors of a recent meta-analysis [ 11 ] showed that there is insufficient evidence to demonstrate the superiority of a rigid brace over a soft brace or no brace. Nevertheless, the most controversial yet widespread use of spinal bracing is in the treatment of non-specific low back pain, be it acute [ 12 ] or chronic [ 13 ]. Although it has been shown that orthoses improve posture and control in patients with non-specific low back pain [ 14 ], the evidence to support this application is scarce [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown an association with paraspinal muscle quality, MC, and presence of low back pain [ 89–93 ], but it remains unknown how treatments to address paraspinal muscle deficits might impact those with vertebrogenic low back pain. A retrospective study of bracing for those with CLBP and MC1 reported short term pain relief [ 94 ]; however, RCTs have questioned the effectiveness of this intervention in general LBP populations [ 95 ].…”
Section: Treatment Of Vertebrogenic Low Back Painmentioning
confidence: 99%